Rural sociology in India - Desai, Akshayakumar Ramanlal (Indian Society of Agricultural Economics, 1961)
Over the years, this historic work, which provides a comprehensive picture of the emergence of rural society in India, has become a classic text. With greater emphasis being placed on rural development for the transformation of the life and conditions of the rural populace, the study of rural society is gaining importance not only among the sociologists and economists but also among the administrators, policy makers and politicians.